S4_1 Pickle Rick: One Rickdiculously Lucky Pickle - Duggan, Matt; Best, Joel; Croxford, Saul (Physics Special Topics, 2017)
We investigate the energy and monochromatic specific intensity of Pickle Rick’s homemade laser gun, which has the god-like power to burn through people. We found the energy to be 2.67MJ, equivalent to 285 AA batteries, and the monochromatic specific intensity to be 1.61 × 1019W m−2sr−1.